Evaluation of genetic variation in Labeo fimbriatus (Bloch, 1795) populations using heterologous primers - Swain, S; Das, S P; Bej, D; Patel, A; Jayasankar, P; Chaudhary, B; Jena, J; Routray, P; Swain, S K; Das, P C; Lakra, W S; Das, Paramananda (Indian Journal of Fisheries, 2013)
The fringe lipped peninsula carp, Labeo fimbriatus, is native to lower peninsular region of India. It is a commercially important species widely fished and consumed throughout much of the tropical and subtropical region of south India. Knowledge of genetic diversity of this species is important to support management and conservation programmes which will subsequently help in sustainable production of this species. DNA markers, mostly microsatellites are excellent tools for evaluation of genetic variation of populations. However, development of these markers from each species is time consuming and costly. Therefore, we studied the usefulness of heterologous markers by assessing the genetic variation of three populations of L. fimbriatus. We examined population structure of L. fimbriatus from different riverine locations in India using rohu microsatellite loci. Out of 30 rohu microsatellite loci, 15 produced amplified products having unambiguous band pattern with clarity in allele scoring. Therefore, these 15 loci were used in 110 samples of L. fimbriatus collected from river Krishna (Vijayawada; n= 30), river Kaveri (Bengaluru; n=50) and river Mahanadi (Sambalpur; n=30). Out of 15 loci, only 3 loci were polymorphic in all the populations and remaining 12 loci were found to be monomorphic. The range of expected heterozygosity values for these polymorphic loci was 0.597 to 0.602. One locus did not satisfy Hardy–Weinberg equilibrium (p=.004) in Kaveri population. Negative inbreeding coefficients (Fis) were found across populations with no significant population structuring (Fst) indicating existence of panmictic populations. As only 3 loci (20%) out of 15 were polymorphic, use of heterologous primers may not be a choice for population studies in L. fimbriatus.